Polymorphisms in the Human Aquaporin 4 Gene Are Associated With Schizophrenia in the Southern Chinese Han Population: A Case–Control Study - Wu, Yung-Fu; Sytwu, Huey-Kang; Lung, For-Wey (Frontiers in Psychiatry, 2020)
Background: Multiple lines of evidence support the pathogenic role of neuroinflammation in psychiatric illness. Through perivascular processes astrocytes contribute to blood–brain barrier (BBB) and form glymphatic drainage system of the central nervous system (CNS). The aquaporin 4 (AQP4) gene, primarily at the end-feet of astrocytes, has been proposed to play putative roles in the clearance of glymphatic system and the development of psychiatric disorders. However, there remain many uncertainties because of the limited research on AQP4. The present study is focused on the association between AQP4 gene polymorphisms and schizophrenia (SCZ) in the Southern Chinese Han population. Methods: 292 patients and 100 healthy controls were enrolled in this study. To study the relationship of AQP4 gene polymorphisms and SCZ, genetic information was drawn from a cohort of 100 healthy controls and 100 matched patients with SCZ of Southern Han Chinese descent. The χ2 test was used to compare allele and genotype distributions between case and control groups. The haplotype and linkage equilibrium were also assessed in two-group comparisons. Results: We detected three SNPs. Patients were observed to have higher frequencies of the T-allele at rs1058424 and the G-allele at rs3763043 than healthy controls had (p = 0.043 and p = 0.045, respectively). Furthermore, the AA genotype at both rs1058424 (p = 0.021, OR = 2.04) and rs3763043 (p = 0.018, OR = 2.25) was associated with a decreased risk of SCZ. The TCG haplotype (p = 0.036) was associated with a potential risk of SCZ, while the ACA haplotype (p = 0.0007) was associated with a decreased risk of SCZ and retained statistical significance after Bonferroni correction (p = 0.006). Conclusions: AQP4 gene polymorphisms are associated with SCZ in the Southern Han Chinese population, which provides an etiological reference for SCZ.